Duality in image-text where imagination and aesthetic simultaneously appear - ศิริกายะ, ศิริชัย; ทองเลิศ, กฤษณ์ (Siam Communication Review, 2017)
The duality of image-text is the co-existance of figurative and discursive symbols. As a result of this duality, the psychological interpretation has lost the perception of the duality of image and text. It is a situational shift of signification. The new aesthetical and original work values have suddenly appeared to a new form of communication work, and the new interpretation occurs. This article places an emphasis on describing the construction and interpretation of the duality of image-text. This is due to the ambiguity between the signification of image and language rules. It is also interesting by the ambiguity from the combination among information, emotion and beauty. Therefore, the seductive potential to the audience has occurred and in turn is, shared in order to create the experience. As a result, the power of stimulating the communicative interactions occurs. This advertising work has creative and aesthetic values. Finally, it tactiles to the minds of each individual person.